2006
DOI: 10.1086/505468
|View full text |Cite
|
Sign up to set email alerts
|

A Survey and Analysis of Spitzer Infrared Spectrograph Spectra of T Tauri Stars in Taurus

Abstract: We present mid-infrared spectra of T Tauri stars in the Taurus star-forming region obtained with the Spitzer Infrared Spectrograph ( IRS). For the first time, the 5-36 m spectra of a large sample of T Tauri stars belonging to the same star-forming region is studied, revealing details of the mid-infrared excess due to dust in circumstellar disks. We analyze common features and differences in the mid-IR spectra based on disk structure, dust grain properties, and the presence of companions. Our analysis encompass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
589
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(637 citation statements)
references
References 100 publications
45
589
2
1
Order By: Relevance
“…Jura et al (2006) also report on the detection of class-C PAH features in a circumstellar disc around the oxygen-rich K-giant HD 233517. Two young objects, the T Tauri star SU Aur (Furlan et al 2006) and the Herbig Ae/Be source HD 135344 (Sloan et al 2005), also show PAH spectra of class C, although in HD 135344 the PAH features seem to be somewhat more in between B and C. This source is also slightly hotter than other class C sources. A comparison of the PAH features in all these sources is given by Sloan et al (2007).…”
Section: Pah Featuresmentioning
confidence: 91%
“…Jura et al (2006) also report on the detection of class-C PAH features in a circumstellar disc around the oxygen-rich K-giant HD 233517. Two young objects, the T Tauri star SU Aur (Furlan et al 2006) and the Herbig Ae/Be source HD 135344 (Sloan et al 2005), also show PAH spectra of class C, although in HD 135344 the PAH features seem to be somewhat more in between B and C. This source is also slightly hotter than other class C sources. A comparison of the PAH features in all these sources is given by Sloan et al (2007).…”
Section: Pah Featuresmentioning
confidence: 91%
“…Following Lada et al (2006), we divide the sample in six spectral type bins. We also show the median SEDs of the ∼2−3 Myr old cluster IC 348 from Lada et al (2006) with dotted curves, of the ∼1−2 Myr old distributed population in Taurus (Furlan et al 2006) with solid curves, and the ∼5 Myr old population in upper Scorpius (Dahm & Carpenter 2009) with dashed curves. For the cluster IC 348, Lada et al (2006) only presents "observed" SEDs.…”
Section: Median Sedsmentioning
confidence: 99%
“…SED spectral index between 1 and 3 mm versus indicators of grain growth from the 10-μm silicate feature. Left SED slope between 1 and 3 mm vs. the ratio between the 10-μm line flux and the continuum as derived from Spitzer/IRS observations by Furlan et al (2006) for the sample of Taurus-Auriga class II YSOs described in R10. Right SED slope between 1 and 3 mm vs. the ratio between the flux at 11.3 and 9.8 μm as derived from Spitzer/IRS observations by McClure et al (2010); the plotted points are all the class II YSOs described in this paper with a value of F 11.3 /F 9.8 reported in McClure et al In the two plots the arrows in the lower left corners show toward which direction the values of the plotted quantities are indicative of the presence of largest grains.…”
Section: Grain Growthmentioning
confidence: 99%